2021
DOI: 10.3389/feduc.2021.645758
|View full text |Cite
|
Sign up to set email alerts
|

Feedback That Leads to Improvement in Student Essays: Testing the Hypothesis that “Where to Next” Feedback is Most Powerful

Abstract: Feedback is powerful but variable. This study investigates which forms of feedback are more predictive of improvement to students’ essays, using Turnitin Feeback Studio–a computer augmented system to capture teacher and computer-generated feedback comments. The study used a sample of 3,204 high school and university students who submitted their essays, received feedback comments, and then resubmitted for final grading. The major finding was the importance of “where to next” feedback which led to the greatest g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Feedback is a central concern of the sample, so the quality and characteristics of the feedback under investigation is important. This was recently demonstrated by Hattie et al (2021), who found that "where to next" feedback led to the greatest gains from the first to the final submission of students' essays.…”
Section: Limitations Of and Directions For Researchmentioning
confidence: 87%
“…Feedback is a central concern of the sample, so the quality and characteristics of the feedback under investigation is important. This was recently demonstrated by Hattie et al (2021), who found that "where to next" feedback led to the greatest gains from the first to the final submission of students' essays.…”
Section: Limitations Of and Directions For Researchmentioning
confidence: 87%
“…It's connected to the teacher's role as a provider for the class. When there is a big gap between where you are and where you want to be, it can inspire you to work more, get more involved, or be more motivated to reach your objective (Hattie et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…One way educators can reduce this uncertainty for students is by providing prompt feedback on both summative and formative assignments. Students also report feeling more valued and are more likely to complete assignments when feedback is given promptly (Hattie et al, 2021).…”
Section: Looking Back and Looking Aheadmentioning
confidence: 99%